Estilo de vida de estudantes de Educaçao Física - Neto, Joao Miguel de Souza (2017)
The main purpose of this is study was to describe the life style and physical activity habits of the Physical Education students from a private Institution of higher Education. With a cross-sectional design study, the sample was formed by 82 students, both genders, recruited in a Physical Education Course, from a private institution of Higher Education, in João Pessoa, Paraíba, Brazil. To collect data, the students answered two questionnaires: The profile of life styles and the Habitual Physical Activity Questionnaire. The data are presented by descriptive statistics, (means, standard deviation and frequencies) and analyzed in SPSS 17.0. The main results showed at least one negative score in each of the five dimensions of the profile of life styles. In this context, stress and nutrition presented higher negative scores. According the Habitual Physical activity, the data showed good scores in physical activity for this sample. However, a significant number of students presented low levels for this variable, consequently, higher levels for bad health status. To conclude, the variable nutrition habits, prevention and interpersonal relationship need more attention from health professionals